Implementasi Metode Balanced Scorecard dalam Pengembangan Sistem Monitoring Pencapaian Key Performance Indicator di Astra Honda Authorized Service Station (AHASS) 01403 - Almila Aulia Kautsar; Adi Purnama (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
This study develops a web-based monitoring system to evaluate the achievement of Key Performance Indicators (KPIs) for mechanics at Astra Honda Authorized Service Station 01403. The main objective is to provide an objective, measurable, and transparent performance assessment method. The system is designed using the Balanced Scorecard (BSC) framework with four perspectives: financial, customer, internal business process, and learning and growth. Indicator prioritization is carried out using the Urgency, Seriousness, and Growth (USG) method, ensuring each KPI aligns with the company’s strategic needs. The application was developed using the Waterfall model. The results show that the application can calculate KPI achievement scores, automatically recap performance data, and present visual dashboards that assist management in evaluating performance. The use of this system has proven to reduce manual input errors and accelerate data-driven decision-making. This system provides benefits in the form of more systematic and objective performance monitoring, and supports continuous improvement at AHASS 01403.